Alkylating agents‐induced gonadotoxicity in prepubertal males: Insights on the clinical and preclinical front - Sruthi Sriram; Tiago Macedo; Annelies Mavinkurve‐Groothuis; Marianne van deWetering; Leendert H. J. Looijenga (Wiley, 2024)
Abstract Rising cure rates in pediatric cancer patients warrants an increased attention toward the long‐term consequences of the diagnosis and treatment in survivors. Chemotherapeutic agents can be gonadotoxic, rendering them at risk for infertility post‐survival. While semen cryopreservation is an option that can be provided for most (post)pubertal boys before treatment, this is unfortunately not an option prepubertal in age, simply due to the lack of spermatogenesis. Over the last couple of years, studies have thus focused on better understanding the testis niche in response to various chemotherapeutic agents that are commonly administered and their direct and indirect impact on the germ cell populations. These are generally compounds that have a high risk of infertility and have been classified into risk categories in curated fertility guidelines. However, with it comes the lack of evidence and the challenge of using informative models and conditions most reflective of the physiological scenario, in short, the appropriate study designs for clinically relevant outcomes. Besides, the exact mechanism(s) of action for many of these "risk" compounds as well as other agents is unclear. Understanding their behavior and effect on the testis niche will pave the way for incorporating new strategies to ultimately combat infertility. Of the various drug classes, alkylating agents pose the highest risk of gonadotoxicity as per previously established studies as well as risk stratification guidelines. Therefore, this review will summarize the findings in the field of male fertility concerning gonadotoxicity of akylating agents as a result of chemotherapy exposure.